Luki informacyjne polskich przedsiębiorstw turystycznych a nowoczesne źródła i metody badań zachowań konsumenckich - Jedlińska, Maja (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The observed development of consumer behaviour theory and practice did not cover, as yet, tourist market. However, it is in this particular market that many information gaps occur, referring, among others, to segmentation criteria, reaction to advertising, shopping plans, evaluation of tourist visits etc. The above will be supported by the author of the hereby analysis. It seems substantial to point to main research problems, which occur in the tourist market including research methods and sources, but also touching upon the existence of many less typical studies, which still require more extensive analysis. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (6); 2006; nr 1145, s. 160-171